Individual performances relative to season bests in major track running championship races are distance-, position- and sex-dependent - Arturo Casado; Andrew Renfree; Beatriz Maroto-Sánchez; Brian Hanley (Asociación Española de Ciencias del Deporte, 2020)
Objectives. To compare season's best times preceding major championships (SBprior) and times achieved in major championship flat track races. Material and methods. 2320 men's and 2312 women's finishing times over 100 m, 400 m, 800 m, 1500 m and 5000 m at the International Association of Athletics Federations (IAAF) World Championships and Olympic Games from 1999 to 2019, and their SBprior, were obtained via IAAF open-access website. Paired t-tests were used to compare major championship times and SBprior for groups across sex in each event. Repeated measures ANOVA was used to examine differences in the percentage of SBprior achieved in the major championship races (%SBprior) between groups and sexes. Results. Finishing time performances were generally slower than SBprior. The difference between SBprior and championship performances increased with distance run and across preliminary rounds and finals. Differences in %SBprior between sexes were found in non-medal finalists in the 800 m and 5000 m (p < 0.001, ES ≥ 0.72). Conclusions. 1500 m and 5000 m athletes competing at major championships should train and be physiologically prepared to sustain non-even paces and produce a fast endspurt to achieve an optimal performance.